PENGARUH KUALITAS PRODUK, CITRA MEREK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN MOBIL HONDA BRIO - Dasmansyah Adyas; Ida Suryani (Institut Teknologi dan Bisnis Dewantara, 2021)
This research aims to determine the effect of Product Quality, Brand Image and Price partially and simultaneously on Purchase Decision and the factor which has the most dominant effect on Purchase Decision of Honda Brio Car in Honda Internusa Cibinong. This populations are consumers who buy and have ever bought a Honda Brio car with samples of 100 people. In this research the technique used is questionnaire method by questionnaire or distributing list of questions to respondents. The analysis method used multiple regression analysis with the help of SPSS v23 application program. From the research results it is obtained that the formed regression equation is Y = 6,780+0,120X1+0,427X2+0,228X3. Partially each variable (Product Quality, Brand Image and Price) has an effect on the purchase decision because the t count > t table and the significance value is < 0,1. Whereas simultaneously variable (Product Quality, Brand Image and Price) has an effect on the purchase decision because the F count is 14,962 > F table 2,14 and the significance score is 0,000. From the determination coefficient test results the Adjusted R square value obtained is 0,297 (29%), where the rest 71% is affected by other factors not examined in this research.